Analisis Pengelolaan Kualitas pada UMKM Es Teh Purnama di Lamongan: Pendekatan Manajemen Operasional - Niayu Rindi Famida; Adita Dwi Nur Anggraini; Hilmy Tata Pradita (Indo Publishing, 2026)
This study aims to examine how the Es Teh Purnama MSMEs in Lamongan, East Java, manage their product quality. Quality management is crucial in running a business, especially for small and medium-sized enterprises in the beverage industry, which rely heavily on product consistency and customer satisfaction. The research method used was a qualitative descriptive approach with a case study design, involving direct observation, in-depth interviews with the owner and employees, and documentation of the production process. The results indicate that Es Teh Purnama has implemented several quality standards in practice, but there are no official documents formalizing them. The main issues identified were inconsistencies in the amount of ice, variations in taste between batches, and the absence of officially documented work guidelines. Using the “Seven Tools of Quality” and the PDCA (Plan-Do-Check-Act) cycle, this study recommends implementing a daily checklist, standardizing standard operating procedures (SOPs), and conducting training programs for employees. Implementing these recommendations is expected to increase customer satisfaction by 15% to 20% and reduce the number of substandard products by up to 30%.